Where Are They Now? Evolution of a Nurse Anesthesia Training School in Ghana and a Survey of Graduates - Potisek, Melissa G.; Hatch, David M.; Atito-Narh, Evans; Agudogo, Jerry; Olufolabi, Adeyemi J.; Rieker, Michael; Muir, Holly A.; Owen, Medge D. (Frontiers in Public Health, 2017)
Ghana, like other countries in sub-Saharan African, has limited access to surgery. One contributing factor is the inadequate number of anesthesia providers. To address this need, Kybele, Inc., a US-based non-governmental organization, partnered with the Ghana Health Service to establish the third nurse anesthesia training school in Ghana. The school, based at Ridge Regional Hospital in Accra, opened in October 2009. This paper describes the evolution of the training program and presents the curriculum. Secondly, the results of a survey conducted among the first four classes of graduates (2011-2014) are presented to determine the strengths and gaps in training and to identify employment locations and equipment availability. Seventy-five of 93 graduates (81%) responded to the survey. The graduates reported working in 39 hospitals across seven of the ten regions in Ghana. Six providers (8%) worked alone and 16 (21%) were one of only two providers. Fifty-three providers (71%) had no physician anesthesiologist at their facility. Most providers had access to basic anesthesia equipment; however, there was limited access to emergency airway equipment. While most graduates felt that their training had prepared them for their current positions, 21% reported experiencing a patient death during anesthesia. The nurse anesthesia training school at Ridge Regional Hospital has been sustained and most of the graduates are working in Ghana, filling an important void. Quality improvement and continuing education must be emphasized in an effort to reduce surgical morbidity and mortality in Ghana.